Evidence that CA3 is Underling the Comorbidity Between Pain and Depression and the Co-curation by Wu-Tou decoction in Neuropathic Pain - Zhu, Chunyan (Sci Rep, 2017)
In neuropathic pain (NP), the atrophy of hippocampus contributes to the comorbidity between pain, depression and the cognitive deficits. However, the exact mechanism underling the comorbidity, the effective control of the degenerations in hippocampus and the remission of the accompanied depressive symptoms are still lacking. Wu-Tou decoction (WTD) has been prescribed for inflammatory pain for thousands of years. In this study, we manifested the effects of WTD on the pain, depression and anxiety co-curative symptoms of NP. Moreover, we reported that WTD rescued the mal-regulated BDNF and TNF-α in hippocampal CA3 alone, which is proven contributing to the pain and induced psychiatric symptoms. Finally, analysis of biochemistry, morphology and electrophysiology exhibited the potential mechanism of WTD in CA3. We found that, in the late stage of SNL condition, WTD mediated the rescue of the down-regulated glutamate as well as its pre-synaptic vesicular glutamate transporters (VGLuT1) and the post-synaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in CA3. In sum, the targeted mediation of glutamatergic system in CA3 suggest that WTD may be responsible for the remission of the hypo-functioned CA3 glutamatergic neurons and further contribute to the co-curative effects of WTD.